THE EFFECT OF INVESTMENT OPPORTUNITY SET (IOS), EARNINGS PERSISTENCE, AND FIRM SIZE ON EARNINGS QUALITY WITH INFORMATION ASYMMETRY AS A MODERATING VARIABLE - Safira Siwi Perwita Kusumawardhani; Dhyah Setyorini (Universitas Tidar, 2024)
This study examines the effect of investment opportunity set (IOS), earnings persistence, and firm size on earnings quality with information asymmetry as a moderating variable. The primary impetus for this study was the number of instances of financial statement manipulation, which indicated that the firm's earnings quality was low and earnings information was subject to change. In 2020-2022, the sample consisted of as many as 15 infrastructure firms listed on the IDX, selected using purposive sampling. This study employed multiple linear regression analysis, and moderated regression techniques to analyze the data. The results of this study showed that earnings quality was unaffected by the investment opportunity set (IOS) and earnings persistence. Meanwhile, the firm size did affect the earnings quality. According to the results of moderated regression analysis (MRA), information asymmetry did not reduce the effect of investment opportunity set (IOS), earnings persistence, and firm size on earnings quality.